Fine-scale bioturbation effects of tubificid worm (Limnodrilus hoffmeisteri) on the lability of phosphorus in sediments. (December 2016) - Chen, Musong; Ding, Shiming; Liu, Ling; Wang, Yan; Xing, Xigang; Wang, Dan; Gong, Mengdan; Zhang, Chaosheng
Abstract: This study investigated the effects of tubificid worm bioturbation on the lability of phosphorus (P) in microcosm sediments. High-resolution dialysis (HR-Peeper) and two types of diffusive gradients in thin films (DGT) (Zr-oxide DGT and ZrO-Chelex DGT) were used to measure soluble P and Fe, and labile P and Fe at a millimeter spatial scale. The worm bioturbation promoted P release (up to 511% of the control) to the overlying water on the 6th day, but it was reduced compared to the control (up to 171% of the control) from the 22nd day to the 102nd day because of the adsorption by Fe(III) oxyhydroxides. The worm bioturbation reduced the pore water soluble P concentration up to 48% and the DGT-labile P concentration up to 29% of the control from a sediment depth of −10 mm to approximately −130 mm before the 22nd day of incubation due to worm ingestion of sediment particles. Two-dimensional measurements of DGT-labile P also showed a much lower concentration of labile P around the worm burrow. This effect disappeared on the 53rd and 102nd day. However, the soluble P and DGT-labile P decreased again up to 41% and 38%, compared to the control from the sediment depth of −20 mm and −10 mm to approximately −130 mm, respectively, on the 152nd day of incubation due to the adsorption by Fe(III) oxyhydroxides. Soluble Fe(II) and DGT-labile Fe did not show significant changes from the worm bioturbation on the 6th day, but decreased up to 31% and 47% of the control after the 6th day. The results that worm ingestion of sediment particles is a significant driver of soluble and labile P reduction in the sediments before the 22nd day. After that, soluble and labile P reduction was attributed to P adsorption by Fe(III) oxyhydroxides. Graphical abstract: Highlights: High resolution techniques were employed to investigate P release from bioturbation sediments. Worm bioturbation decreased the concentration of soluble/labile P in sediments before the 22nd day. Bioturbation effects disappeared on the 53rd and 102nd day and emerged again on the 152nd day. The P decreased because of ingestion by worm and adsorption by Fe(III) oxyhydroxides. Abstract : Tubificid worm bioturbation decreased the lability of P in sediments.